2008
DOI: 10.1111/j.1472-765x.2008.02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of isolates of Beauveria bassiana obtained from overwintering and summer populations of Sunn Pest (Eurygaster integriceps)

Abstract: Aim:  To examine whether isolates of the entomopathogenic fungus Beauveria bassiana are more closely associated to their summer hosts compared with overwintering hosts, with recently developed molecular tools based on mitochondrial regions. Methods and Results:  Primers for the traditional ITS1‐5·8S‐ITS2 region and two mitochondrial intergenic regions, namely, nad3‐atp9 and atp6‐rns, were used. All amplified products were sequenced, aligned and Neighbour‐Joining (NJ), parsimony and Bayesian phylogenetic infere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
5
0
7
Order By: Relevance
“…An increasing number of studies point towards a broad correlation of fungal isolates with their place of origin and/or habitats [e.g., [18,21,30,59,60]]. Obviously, the factors that can influence B. bassiana population structures are many and can include: climate conditions, the range of temperatures in which the various isolates can grow in nature, humidity levels, UV exposure, habitat, cropping system and soil properties [18,27,59,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies point towards a broad correlation of fungal isolates with their place of origin and/or habitats [e.g., [18,21,30,59,60]]. Obviously, the factors that can influence B. bassiana population structures are many and can include: climate conditions, the range of temperatures in which the various isolates can grow in nature, humidity levels, UV exposure, habitat, cropping system and soil properties [18,27,59,61].…”
Section: Discussionmentioning
confidence: 99%
“…In other mitosporic entomopathogenic fungi, such as Metarhizium [27], Lecanicillium [28] and Nomurea [29], mtDNA data compared favourably to data based on ITS combined with a single nuclear gene, for applications in phylogeny, taxonomy and species or strain -identification. In Beauveria , the use of mtDNA RFLPs or partial mtDNA sequences suggested that mtDNA can be equally useful for such studies [2,30]. …”
Section: Introductionmentioning
confidence: 99%
“…In other fungal genera, like Lecanicillium , Verticillium, and Beauveria , the use of mitochondrial (mt) genes and mt intergenic regions proved an extremely useful tool to reveal species differences within a genus and even helped to resolve taxonomic ambiguities (e.g., the small rRNA subunit ( rns ), the NADH dehydrogenase subunits 1 ( nad 1) and 3 ( nad 3), the mt intergenic domains nad 3– atp 9 and the atp 6- rns ) [2527]. Similarly, other nuclear regions/genes like the RNA polymerase II largest subunit gene ( rpb 1) and the IGS region of the rRNA repeat also proved to be excellent tools for discriminating species within Metarhizium, Verticillium and Aspergillus [23, 27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…( sensu lato ), and also that EF1-α sequences provide adequate information for the inference of relationships in this genus [8]. Studies on the genetic variability of BCAs such as B. bassiana are crucial for the development of molecular tools for their monitoring in the natural environment [6]. …”
Section: Introductionmentioning
confidence: 99%